2007
DOI: 10.1002/ange.200603386
|View full text |Cite
|
Sign up to set email alerts
|

In Situ High‐Energy Synchrotron Radiation Study of Sol–Gel Nanoparticle Formation in Supercritical Fluids

Abstract: Nanostructured materials have drawn much attention because of the dramatically different properties observed on going from bulk material to nanosized particles. Nanoparticles have properties that lie between the quantum effects of atoms and molecules and the bulk properties of materials. In the nanometer range (1-100 nm) the particle size affects structural characteristics (e.g., lattice symmetry, unit-cell dimension), electronic properties (e.g., band gap), and therefore also the physical (e.g., wetting, melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…The main conclusion of the study by Jensen et al [29] of the formation of TiO 2 in supercritical CO 2 was that the nucleation and growth in supercritical CO 2 follow the same pattern as the conventional sol-gel synthetic route, but on a much faster timescale. The general pattern for the formation of a solid in solution (or sol-gel reaction synthesis) consists of four periods: 1) The induction period, 2) the latent period, 3) the precipitation period, and 4) the slow growth period.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The main conclusion of the study by Jensen et al [29] of the formation of TiO 2 in supercritical CO 2 was that the nucleation and growth in supercritical CO 2 follow the same pattern as the conventional sol-gel synthetic route, but on a much faster timescale. The general pattern for the formation of a solid in solution (or sol-gel reaction synthesis) consists of four periods: 1) The induction period, 2) the latent period, 3) the precipitation period, and 4) the slow growth period.…”
Section: Resultsmentioning
confidence: 97%
“…SAXS data contain information on particle size independent of the crystallinity of the particle. The first in situ SAXS/WAXS study of supercritical reactions was reported by Jensen et al, [29] who synthesized TiO 2 in supercritical CO 2 . The data revealed that nanoparticle formation follows the same progression as seen in conventional solvothermal reactions, but on a much faster timescale.…”
Section: Introductionmentioning
confidence: 99%
“…[236] The supercritical sol-gel process offers the considerable advantages of low reaction temperature (100 8C) and a fast time scale (ca. 50 min) compared to the corresponding conventional strategy.…”
Section: In Situ Small-angle X-ray Scattering (Saxs)mentioning
confidence: 99%
“…On one hand, crystalline TiO2 seems to be more effective than amorphous titania to prevent recombination of electrons (e -) and holes (h + ) [17]. Maybe because of that, most references just deal with the characterization of crystalline TiO2, setting aside the analysis of the amorphous contribution, leaving unregarded the degree of crystallinity and the fact that amorphous titania could have some positive influence [17][18][19][20][21][22]. On the other hand, while in some works anatase is considered as the most photoactive TiO2 crystalline phase [23][24][25], other published papers state that materials containing different TiO2 polymorphs (mainly anatase with some rutile) are more active in oxidation processes [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%